Cutaneous Leishmaniasis in a Bangladeshi Adult: A Case Report - Rahim, Abdur; Moniruzzan, Md; Hassan, Rashedul; Sarmin, Monira; Yusuf, Md Abdullah; Ahmed, Be Nazir; Rahman, Md Mujibur (Bangladesh Journal of Medicine, 2015)
Cutaneous leishmaniasis is rare in Bangladesh although very few case reports are seen since last few years. But Visceral Leishmaniasis (kala azar) and PKDL are common in this region. In country like ours where tuberculosis and leprosy are more prevalent Cutaneous Leishmaniasis is very likely to be mistreated as Cutaneous tuberculosis especially lupus vulgaris or leprosy. Cases of Cutaneous Leishmaniasis (CL) are usually imported to Bangladesh from other endemic countries. A patient from an endemic area of Cutaneous Leishmaniasis, a non-healing nodulo-ulcerative lesion on exposed part of the body, dermal infiltration with lymphocytes, histiocytes and plasma cells and demonstration of intracellular parasites in lesional skin establish the diagnosis of Cutaneous Leishmaniasis. We present a case of Cutaneous Leishmaniasis in a Bangladeshi adult working in Saudi Arabia for more than 15 years. He presented with multiple ulcerative lesions on nasal bridge, right ear lobule and dorsum of right ring finger. The patients clinical history, morphology of the lesions and laboratory analysis were consistent with Cutaneous Leishmaniasis, a rare entity for Bangladesh. Bangladesh J Medicine Jul 2014; 25 (2) : 78-80